Econometric Analysis of Different Type of Institutions Effect on Education Expenditure in Pakistan - Samar Ali; Rana Muhammad Usman Khan; Muhammad Waqar; Saif Ullah; Muhammad Ehsan Elahi (Social Science Review Archives, 2025)
The spending on education for the families residing in Pakistan is evaluated in this study. The data used for this analysis is PSLM (Pakistan Social and Standard Living Measurement) for the year 2018–19. It examines the elements and variables that contribute to the families' total educational costs. The estimation results indicate that the amount of money a family spends on education depends on the family number of children, different type of colleges and university and institutions, and the degree levels of the children living in the four provinces of Pakistan. However, it is revealed that every factor has a favorable impact on the policy recommendations for the families of Pakistan interested for the attainment of education. Every discovery may also have an effect on various educational system-related problems. Each of these factors influences the amount of money that households spend on education differently. The regression will be executed using the regression analysis technique and the OLS (Ordinary Least Square) Method. This approach and methodology considered to carry out the regression when a model contains quantitative dependent variable. Estimates and outcomes will be initiated to implement the plan. It will provide solutions for any issues that can be explained by the variables pertaining to family education spending.